2011
DOI: 10.1002/pc.21210
|View full text |Cite
|
Sign up to set email alerts
|

Mode I interlaminar fracture toughness of Nylon 66 nanofibrilmat interleaved carbon/epoxy laminates

Abstract: Carbon/epoxy laminates interleaved with laboratory scale electrospun Nylon 66 nanofibrilmat and spunbonded nonwoven mats were investigated. The effect of the nanoscale fibers on the fracture toughness of the composite under pure Mode I loading was evaluated. It was shown that the nanofibrilmat is responsible for a major interlaminar fracture toughness improvement, as high as 255–322%, compared to a noninterleaved carbon/epoxy reference laminate. We further studied the improvement mechanism of the electrospun n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…The effect of PA 6.6 nanofibres on woven laminates has been studied by Hamer et al [18] and Palazzetti et al [20,21]. Although Hamer et al report an increase in G Ic , only minor improvements and even decreases on both G Ic and G IIc are reported by Palazetti et al [18,20,21]. De Schoenmaker et al [14] state that G Ic increases slightly upon addition of PA 6 nanofibres in UD laminates.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The effect of PA 6.6 nanofibres on woven laminates has been studied by Hamer et al [18] and Palazzetti et al [20,21]. Although Hamer et al report an increase in G Ic , only minor improvements and even decreases on both G Ic and G IIc are reported by Palazetti et al [18,20,21]. De Schoenmaker et al [14] state that G Ic increases slightly upon addition of PA 6 nanofibres in UD laminates.…”
Section: Introductionmentioning
confidence: 92%
“…However, these improvements in G Ic only occur during precracking or crack initiation, while G Ic was not affected or even decreased at further crack growth. The effect of PA 6.6 nanofibres on woven laminates has been studied by Hamer et al [18] and Palazzetti et al [20,21]. Although Hamer et al report an increase in G Ic , only minor improvements and even decreases on both G Ic and G IIc are reported by Palazetti et al [18,20,21].…”
Section: Introductionmentioning
confidence: 92%
“…It has also been shown that certain nanofibre veils can be used to improve the compression after impact (CAI) [4], delamination resistance and the Mode I [5] and Mode II interlaminar fracture toughness (ILFT) of composites http://dx.doi.org/10.1016/j.compositesa.2015.01.028 1359-835X/Ó 2015 Elsevier Ltd. All rights reserved. [6][7][8][9][10]. Nanofibre veils have also been shown to improve the fatigue resistance [2,11] and vibration damping [12] properties of fibre reinforced composite materials.…”
Section: Introductionmentioning
confidence: 97%
“…Totally, in modified specimen, it was observed that the mode I and II fracture toughness have increased 17–120% respect to neat specimen. Hamer et al investigated the carbon/epoxy laminates interleaved with Nylon 66 nanofibrilmat and spunbonded nonwoven mats. The effects of the nanoscale fibers on the mode I fracture toughness of the composite specimens were evaluated.…”
Section: Introductionmentioning
confidence: 99%